An unconditional prenatal cash benefit is associated with improved birth and early childhood outcomes for Metis families in Manitoba, Canada. (February 2021) - Struck, Shannon; Enns, Jennifer E.; Sanguins, Julianne; Chartier, Mariette; Nickel, Nathan C.; Chateau, Dan; Sarkar, Joykrishna; Burland, Elaine; Hinds, Aynslie; Katz, Alan; Santos, Rob; Chartrand, A. Frances; et al.
Highlights: A cash benefit was associated with better birth outcomes for low-income Metis families. Among families who received the benefit, there were fewer low birth weight and preterm births. Children in families who received the benefit were more likely to be fully vaccinated by age 2. Abstract: Background: In Manitoba, low-income pregnant women are eligible for the Healthy Baby Prenatal Benefit (HBPB), which provides up to CAD $81.41/month during the second and third trimesters of pregnancy. In research conducted in partnership with the Manitoba Metis Federation, we examined the association of the HBPB with Metis birth and early childhood outcomes. Methods: Using the whole-population administrative data repository at the Manitoba Centre for Health Policy, we identified all Metis women who gave birth in Manitoba 2003–2011 and limited the cohort to women who were low-income (receiving income assistance during pregnancy; n = 4891). We adjusted for differences between the treatment (received HBPB; n = 3702) and control (did not receive HBPB; n = 1189) groups with propensity score weighting, and then used propensity score weighted regressions to compare birth and early childhood outcomes between the groups. Results: Receiving the HBPB was associated with a lower risk of low birth weight (adjusted Relative Risk [aRR] 0.74; 95% CI 0.59, 0.94) and preterm (aRR 0.78; 95% CI 0.65, 0.94) births, a higher risk of large-for-gestational-age births (aRR 1.21; 95% CI 1.06, 1.39) and neonatal readmission within 28 days (aRR 1.58; 95% CI 1.05, 2.37). HBPB receipt was also associated with increased childhood vaccinations at age 1 (aRR 1.08; 95% CI 1.00, 1.15) and 2 (aRR 1.12; 95% CI 1.06, 1.18). We observed no significant associations for Apgar scores, small-for-gestational-age births, breastfeeding initiation, birth hospitalization length of stay or child development scores. Conclusion: A modest unconditional prenatal benefit provided to low-income Metis women was associated with improved birth outcomes and child vaccinations; however, an association with increased large-for-gestational-age births may warrant further exploration. Lack of significant associations between HBPB and child development measures suggests more sustained support may be necessary to improve longer-term outcomes.